2022
DOI: 10.3390/ijms23137412
|View full text |Cite
|
Sign up to set email alerts
|

Identification of BcARR Genes and CTK Effects on Stalk Development of Flowering Chinese Cabbage

Abstract: Flowering Chinese cabbage (Brassica campestris L. ssp. Chinensis var. utilis Tsen et Lee) is an important and extensively cultivated vegetable in south China, whose major food product is the stalk. In the process of stalk formation, its initiation and development are regulated by a series of hormonal signals, such as cytokinin and gibberellin. In this study, we analyzed the effects of zeatin (ZT) and gibberellin A3 (GA3), and their interaction, on the bolting of flowering Chinese cabbage. The results indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 64 publications
(90 reference statements)
0
10
0
Order By: Relevance
“…In Brassica campestris , CTK may affect bolting by affecting myeloid cell size and cell cycle gene expression levels to reduce plant height and increase stem diameter. Five key genes ( ARR1-B , ARR2-A , ARR10 , ARR12 and ARR14 ) are highly expressed in different tissues at eight stages ( Ou et al., 2022 ). Studies have found that the number of potato tubers increases during CTK accumulation while individual tuber weight decreases ( Tao et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brassica campestris , CTK may affect bolting by affecting myeloid cell size and cell cycle gene expression levels to reduce plant height and increase stem diameter. Five key genes ( ARR1-B , ARR2-A , ARR10 , ARR12 and ARR14 ) are highly expressed in different tissues at eight stages ( Ou et al., 2022 ). Studies have found that the number of potato tubers increases during CTK accumulation while individual tuber weight decreases ( Tao et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The genetic mechanism and regulation of succulent stem formation in Chinese kale is still unclear. Therefore, the genetic mechanism of stem formation of Chinese kale and its hybrids could reference from that of storage organ formation in other crops, e.g., potato tubers ( Kondhare et al., 2020 ; Kolachevskaya et al, 2021 ; Kondhare et al., 2021 ; Saidi and Hajibarat, 2021 ), radish taproot ( Yu et al., 2016 ; Xie et al., 2018 ; Xie et al., 2020 ), sweetpotato tuberous root ( Zierer et al., 2021 ), lotus rhizomes ( Yang et al., 2015 ), the bolting stem of flowering Chinese cabbage ( Huang et al., 2017 ; Kou et al., 2021 ; Ou et al., 2022 ), etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that overexpression of POTH1 (potato homeobox 1) results in lower levels of GA20ox1 (a key rate-limiting enzyme in the synthesis of GA) transcription ( Rosin et al., 2003 ) Moreover, in Arabidopsis , GA3ox1 (GA-biosynthesis gene) transcript shows no difference in KNOX1-overexpression plants ( Hay et al., 2002 ), indicating that GA20ox1 is a specific target in the GA-biosynthesis pathway for KNOX proteins. Several recent studies have revealed that gibberellin and cytokinin play vital roles throughout bolting and flowering ( Guan et al., 2021 ; Ou et al., 2022 ). Meanwhile, our preliminary results indicated that GA and cytokinin exert antagonistic effect on bolting in flowering Chinese cabbage ( Ou et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have revealed that gibberellin and cytokinin play vital roles throughout bolting and flowering ( Guan et al., 2021 ; Ou et al., 2022 ). Meanwhile, our preliminary results indicated that GA and cytokinin exert antagonistic effect on bolting in flowering Chinese cabbage ( Ou et al., 2022 ). We may speculate that BcKNOX family have significant functions in bolting and flowering of flowering Chinese cabbage yet to be discovered.…”
Section: Introductionmentioning
confidence: 99%